So-Called Butcher's Warts Appeared on the Hands of a Meat Handler - Kazunori Miyata; Usho Go; Tsuyoshi Mitsuishi (Karger Publishers, 2020)
We present a case of so-called butcher's warts in a meat handler with atopic dermatitis. PCR with direct sequence analysis confirmed the presence of HPV 7 in the hand warts of the patient. Histopathologically, the lesion contained vacuolated cells with centered nuclei, and there were no abundant keratohyalin granules in the granular layer. Clinically, HPV 7-induced warts tend to appear on the hands of meat/fish handlers or cutters in the world. Therefore, meat/fish had been thought to act as a vector for the transmission of HPV 7. In our case, the Japanese patient's occupation required the handling of meat/fish products, and HPV 7 was found from his hand warts. This evidence indicated that HPV 7 was widely distributed in the world. However, this patient worked in a Japanese restaurant, which required the handling of meat/fish products with tools such as knives and chopping boards. Therefore, we suggested that HPV 7 might be correlated with specific reservoirs.